2016
DOI: 10.1111/nyas.13025
|View full text |Cite
|
Sign up to set email alerts
|

Yoga in school settings: a research review

Abstract: Research on the efficacy of yoga for improving mental, emotional, physical, and behavioral health characteristics in school settings is a recent but growing field of inquiry. This systematic review of research on school-based yoga interventions published in peer-reviewed journals offers a bibliometric analysis that identified 47 publications. The studies from these publications have been conducted primarily in the United States (n = 30) and India (n = 15) since 2005, with the majority of studies (n = 41) condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
72
1
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(81 citation statements)
references
References 87 publications
3
72
1
5
Order By: Relevance
“…In a bibliometric analysis, 47 publications on yoga in school settings were identified [12]. These studies were conducted primarily in the U.S. (N ¼ 30) and India (N ¼ 15).…”
Section: Assessment Methodsmentioning
confidence: 99%
“…In a bibliometric analysis, 47 publications on yoga in school settings were identified [12]. These studies were conducted primarily in the U.S. (N ¼ 30) and India (N ¼ 15).…”
Section: Assessment Methodsmentioning
confidence: 99%
“…Yoga is being increasingly taught in school settings as a strategy to enhance student health, well-being, and performance (Butzer et al 2015), with systematic analyses (Ferreira-Vorkapic et al 2015; Serwacki and Cook-Cottone 2012) and narrative reviews (Butzer et al 2016; Khalsa and Butzer 2016) revealing preliminary evidence for the benefits of yoga in schools. For example, Khalsa and Butzer (2016) conducted a bibliometric analysis of research on school-based yoga programs and identified 47 studies, most of which reported beneficial effects of school-based yoga on student outcomes such as psychological well-being, academic performance, and health-related measures.…”
Section: Introductionmentioning
confidence: 99%
“…Scientific investigations of the health benefits of yoga have increased over the past twenty years (Cramer et al, 2014; Jeter et al, 2015; Khalsa et al, 2016; Field, 2016). Overall, research suggests that yoga can offer physical and mental health benefits (Bussing et al, 2012; Khalsa et al, 2016; Streeter et al, 2012), and improvements in sleep (Khalsa et al, 2004; Mustian et al, 2013; Wang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, research suggests that yoga can offer physical and mental health benefits (Bussing et al, 2012; Khalsa et al, 2016; Streeter et al, 2012), and improvements in sleep (Khalsa et al, 2004; Mustian et al, 2013; Wang et al, 2015). However, racial/ethnic minorities and individuals of low SES remain underrepresented demographics in the existing yoga literature.…”
Section: Introductionmentioning
confidence: 99%